Community Resilience under the Impact of Urbanisation and Climate Change : Cases and Experiences from Zimbabwe - Mabeza, Christopher M.; Chirisa, Innocent (Book collections on Project MUSE., 2019)
As the world today faces messy problems, what in some circles has been called global weirding, the term resilience has taken centre stage. This is crunch time--as we grapple with the negative effects of both climate change and urbanisation. Some commentators have compared the huge problems we face today to Oom Schalk's proverbial leopard waiting for us in the withaak's shade. Do we endlessly count Oom Schalk's proverbial leopard's spots? This is the question posed by a stellar cast of academics, researchers, and experts whose contributions in this text is a rallying cry for action to build resilience to the challenging impact of urbanisation and climate change. To that end, this volume gives hope about the potential for human agency. Our challenge however, is to re-examine our values, to change our conservation conversation and return to a more wise and holistic understanding of ourselves and our place in the Universe. Perhaps, then only can the obituaries on our demise stay locked in the drawer.